Resolving conflict communication of multinational mining companies: PT Vale Indonesia and the local community - Nur Azizah Fitrianti; Andre Noevi Rahmanto; Sudarmo Sudarmo (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
The conflict between PT Vale Indonesia and the Kuari community in East Luwu Regency demonstrates the ongoing clash between the company's legal rights to mining land and the community's dependence on the same land for housing and livelihoods. This research investigates the communication dynamics underlying the conflict through a qualitative case study method, using in-depth interview techniques with 12 informants from the company, local government and community. The results showed that formal meetings held through formal and informal dialog facilitated dialog on land access and use. The shift of some community attitudes from protest to limited engagement demonstrates the effectiveness of the dialog. Although, the core contradiction between state-sanctioned legality and community-based recognition remains. Applying Relational Dialectics Theory, this research shows how unequal discourses shape community and company interactions. The research recommends strengthening inclusive dialogue and recognition of community-based land management to promote more stable and equitable company-community relations.